2013
DOI: 10.1002/ajpa.22254
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Reliability of suchey‐brooks and buckberry‐chamberlain methods on 3D visualizations from CT and laser scans

Abstract: visualizations based on CT-scans and, for the first time, on 3D visualizations from laser scans.We examined how the bone features can be evaluated on 3D visualizations and whether the different modalities (direct observations of bones, 3D visualization from CT-scan and from laser scans) are alike to different observers. We found the best inter-observer agreement for the bones versus 3D visualizations, with the highest values for the auricular surface. Between the 3D modalities, less variability was obtained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 16 publications
5
31
0
2
Order By: Relevance
“…Finally, the studies (Villa et al. ; Wink, ) also reported a greater variability among the observers than those found in Telmon et al. study.…”
Section: The Use Of 3d Segmentation To Mimic the Appearance Of Dry Bonementioning
confidence: 65%
See 1 more Smart Citation
“…Finally, the studies (Villa et al. ; Wink, ) also reported a greater variability among the observers than those found in Telmon et al. study.…”
Section: The Use Of 3d Segmentation To Mimic the Appearance Of Dry Bonementioning
confidence: 65%
“…() and Villa et al. () highlighted the importance of the experience in evaluating digital images and the importance of using correct scanning parameters for obtaining an accurate 3D model. Finally, the studies (Villa et al.…”
Section: The Use Of 3d Segmentation To Mimic the Appearance Of Dry Bonementioning
confidence: 99%
“…Background documentation on relevant factors for individuals is likely more plentiful and more reliable, facilitating better controlled studies. High resolution CT scanning offers sufficient resolution for application of cranial suture closure (Harth et al, 2010), sternal rib end (Dedouit et al, 2008) and pubic symphysial (Lottering et al, 2014;Telmon et al, 2005) methods, although visualizing the more subtle alterations at the auricular surface has, thus far, proven problematic (Barrier et al, 2009;Villa et al, 2013). High resolution CT would potentially enable study of age indicators in autopsy specimens and in living individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it has been suggested that 3D visualization of the bones could be generated from CT scans and the methods could then be applied to them, but their Villa C., Hansen M.N., Buckberry J., Cattaneo C., Lynnerup N. 2013. Forensic age estimation based on the trabecular bone changes of the pelvic bone using post-mortem CT. Forensic Science International 233(1-3):393-402. l application is unreliable: some papers report good agreement between the modalities [6], others suggest using the methods developed on dry bones with caution and refer to reduce accuracy [7,8] [8].…”
Section: Introductionmentioning
confidence: 99%